Analisis User Experience pada Penggunaan Jakone Mobile - Inas Qoniah; Pantra Wijaya; Putri Indah Oktavia; Raissa Raissa; Rizka Anggraeni; Asep Taryana (Journal of Technopreneurship on Economics and Business Review, 2022)
In the digital era, Indonesia has developed with the latest technology which is one part of the company in order to survive and exist. Likewise, one of the government bank, Bank DKI, which is engaged in financial services, utilizes the latest technology, namely information communication technology (ICT). With this technology, the company innovates by launching a mobile banking application JakOne Mobile. The purpose of this research is to see that the quality of service will affect the level of user satisfaction (user experience) and to see the effectiveness of the product innovations carried out by Bank DKI (JakOne Mobile). The method used in this research was the User Experience Questionnaire (UEQ). The results of the study explains that the JakOne Mobile application is included in the "good" category. However, it still requires improvement in the application because from the usability aspect it gets the lowest score, this is because there are still errors in terms of usage, these results are expected to be considered by Bank DKI.